Application of Statistical Tests in Measuring the Influence of Product Quality and Brand Image - Henaulu, Agung K; Eki Wulansari, Vovia; Dahlia Kaisupy, Tina; Abdulmudy, Reza; Salampessy, Haris; Mony, Farida; Latukau, Azizah (UNIPA PRESS, 2025)
The purpose of this study is to investigate how brand image and product quality have an impact on the interest in buying precious metals at the Sleman Branch Pawnshop. The study found that product quality, which includes purity, authenticity, and attractive design, significantly affects consumer buying interest. The quantitative methods used include survey methods and multiple regression analysis. In addition, Pegadaian's reputation as a safe and reliable financial institution greatly influences customers' desire to buy precious metals. The results of the regression analysis show that product quality has a regression coefficient of 0.543 with a p-value < 0.001, while brand images have a regression coefficient of 0.479 with a p-value < 0.001. The synergy between brand image and product quality shows an increase in customer buying interest. These two factors influence each other's purchase decisions. The implications of this study show that, in order to maintain and increase consumer buying interest, Pegadaian must continue to maintain and improve the quality of its products and brand image. This research provides valuable insights for pawnshops on how to optimize marketing strategies and product quality management